Equity in Financing and Distribution of Health Benefits in Zambia : Health Equity and Beneficiary Incidence in Zambia - Chansa, Collins; Workie, Netsanet Walelign; Chitah, Bona; Kaonga, Oliver (World Bank, Washington, DC, 2019)
The Zambian health care system continues to undergo various reforms. The system has experienced health financing and organizational reforms since 2006. Among the notable and common themes underpinning all the health reforms across the different timelines have been the following: the policy commitment continues to be associated with the desire to ensure that resources and health care services are distributed and provided as close to the household or family as possible; and access to quality and affordable health care services continues to be one of the central themes of the reform process. In this regard, health services are supposed to be generally available, adequate, and of reasonable quality and cost. Given that a number of health financing reforms have been implemented in Zambia over the years, this study provides an updated analysis on the extent to which government expenditures on health provide an effective intervention in redistributing health care resources in an equitable manner. The study looks at the health system holistically and does not look at each of the individual reforms.